ANALISIS TINGKAT PENGGUNAAN (USABILITY) DAN KESADARAN MEREK (BRAND AWARENESS) APLIKASI TRANSPORTASI ON LINE TERHADAP KEPUASAAN PELANGGAN GENERASI Z DI YOGYAKARTA - Heni Kusumawati; Maria Jawa Tukan (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to examine the effect of usability and brand awareness on the selection of online transportation on customer satisfaction and test different factors of usage rate and brand awareness of online transportation as purchasing decisions for Generation Z transportation services in Yogyakarta. The data collection method used is purposive sampling. The respondents in this study were Generation Z users of Grab and Go-jek online transportation applications in Yogyakarta. The number of samples used was 172 respondents aged 17-30 years. Male respondents amounted to 65 people (37.8%) and women amounted to 107 people (62.2%). Based on employment status, 84.5% are still students or university students and 15.5% are employed. The results showed that: a) the level of use has a positive effect on online transportation customer satisfaction, b) brand awareness has a positive effect on online transportation customer satisfaction, c) there are differences in the level of use of online transportation applications on customer satisfaction, and d) there is no difference in brand awareness of Grab and Go-jek online applications on customer satisfaction.